Post-Conflict Security Sector and Public Finance Management : Lessons from Afghanistan - World Bank (Washington, DC, 2012)
In recent years, international organizations like OECD and the World Bank have concluded that standard principles of Public Finance Management (PFM) are equally applicable to all areas of the national budget, including the security sector. To date however, very few reviews of PFM systems have included the security sector, not least because many governments tend to be overly protective about scrutiny of public finances in this sector, and as a result most donors have been reluctant to engage. As a result, the bulk of public expenditure reviews have focused on non-security components of the national budget, which represent an important but incomplete slice of national spending. Despite growing awareness of the importance of extending PFM reviews to the security sector, so far the challenge of moving beyond basic principles toward the adoption of a more comprehensive approach to building an effective and fiscally sustainable post-conflict security sector remains elusive. In countries such as Afghanistan, Iraq and Sierra Leone, national authorities and donors are struggling to regain control of unaffordable levels of security sector spending, much of it financed directly by donors. In many cases long-term external assistance may be required for the security sector, generating severe trade-offs with other priority sectors which also require long-term external support. Overcoming the legacy of a fiscally unsustainable and poorly managed security sector calls for full application of PFM principles to support the establishment of checks and balances required to establish a wholly accountable security sector.